O despertar de um sonho: a inserção do turismólogo no mercado de trabalho de Salvador - Ba - SANTOS, Edimiria Góes César (2015)
This work is the result of research that sought to find answers about the integration of turismólogos in Soteropolitano labor market by analyzing the positions held and the average income of these professionals. In addition, it was intended to raise the main barriers to the uptake of Tourism professionals by the labor market verifying the performance of graduates since the creation of the course to the present day. In this way, you could realize the importance of higher education in Tourism for insertion or not these professionals in the tourist trade. Thus, the methodological approach used was the inductive method. Through descriptive and field research it was possible to investigate the characteristics of the Bachelors in Tourism Salvador sample selected analyzing their professional activities since graduated to the status of how and where they currently are. The results achieved have concluded that a significant portion of graduates still in the tourist market. However, many did not have the same opportunities, given the lack of professional market reserve, or not yet sought a tourist segment that was stable, thus resulting in the insertion in other areas of professional practice. It is hoped that this research contribute to the analysis of the intersection of the tourist market and training in Tourism in the city of Salvador.